A new mite species of Pseudoparasitus Oudemans (Acari: Mesostigmata: Laelapidae), and a key to known Iranian species of the genus - Shahrooz Kazemi (Persian Journal of Acarology)
Pseudoparasitus hajiqanbari sp. nov., a new free-living species of the family Laelapidae is described based on adult females collected from forest litter in southeastern Caspian Sea, Mazandaran and Golestan Provinces, Iran. The new species can be easily distinguished from other members of the genus by a combination of characters, including presence of eight denticulate rows in deutosternal groove, edentate fixed digit of chelicerae, elongate post-stigmatic region of peritrematal shield and insertion of palp trochanter setae av1 on a protuberance. Also, a key to the known Iranian species of Pseudoparasitus Oudemans is provided.